Reporting of lifetime fractures: methodological considerations and results from the Thai Cohort Study - Berecki-Gisolf, Janneke (BMJ Group, 2012)
OBJECTIVES: To provide estimates of fracture incidence among young adults in Thailand. DESIGN: Cross-sectional analysis of a large national cohort. SETTING: Thailand. PARTICIPANTS: A total of 60 569 study participants residing nationwide responded to the 2009 follow-up survey; 55% were women and median age was 34 years (range 19–92). OUTCOME MEASURES: Self-reported lifetime fractures, along with age at fracture. Fracture incidence rates per person-year were then compared using lifetime fracture reports, and again selecting only fractures reported for the last year. Incidence rates were compared by age and sex. RESULTS: 18 010 lifetime fractures were reported; 11 645(65%) by men. Lifetime fracture prevalence was 30% for men and 15% for women. Lifetime incidence per 10 000 person-years was 83; analysing only fractures from the last year yielded a corresponding incidence rate of 187. For ages 21–30, fractures per 10 000 person-years were more common among men than women (283 (95% CI 244 to 326) and 150 (130 to 173), respectively); with increasing age, rates decreased among men and increased among women (for ages 51–60, 97 (58 to 151) and 286 (189 to 417), respectively). CONCLUSIONS: Large-scale surveys provide a feasible method for establishing relative fracture incidence among informative subgroups in a population. Limiting analyses to fractures reported to have occurred recently minimises bias due to poor recall. The pattern of self-reported fracture incidence among Thais aged 20–60 was similar to that reported for Western countries: high falling rates in young men and high rising rates in older women.